U.S. Copyright Renewals, 1974 January - June - Library of Congress. Copyright Office (Salt Lake City, UT : Project Gutenberg, 2004)
"U.S. Copyright Renewals, 1974 January - June" is a reference publication detailing renewal registrations of various literary works, pamphlets, serials, and contributions to periodicals, likely compiled in the early 1970s. This resource is arranged by registration number and includes curated entries that offer information on both the original and renewed copyrights for a wide range of media, highlighting a variety of authors and topics, such as popular comic books and notable contributions to periodicals. The opening of this work presents an organized list of titles and related information about renewal registrations, showcasing entries like those for "Superman" comics and works by authors such as Victoria Case and Edgar Rice Burroughs. Each entry details the initial copyright date, registration information, and notes on contributions to specific magazines. This systematic presentation serves as an essential tool for researchers and copyright professionals interested in tracking the copyright status of popular publications from this time period. (This is an automatically generated summary.)
Release date is 2004-03-01
Produced by Michael Dyck, Charles Franks, pourlean, and the Online Distributed Proofreading team, using page images supplied by the Universal Library Project at Carnegie Mellon University
Keywords: Copyright -- United States -- Catalogs